Application of Learning Management System (LMS) Simpai 7 as A Means of Learning Social Studies at Junior High School 7 Bandung - Prayogi, Dimas Dwi; Supriatna, Nana; Kusmarni, Yani (Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
The availability of adequate learning facilities must support the achievement of a marginal learning process. This study aims to manage and describe social studies teachers implementing the SIMPAI 7 Learning Management System (LMS) as a learning tool at Junior High School 7 Bandung. This study uses a qualitative approach with a descriptive method. The research informants were a student of classes VI C, VI E, and VII H and teachers of Junior High School 7 Bandung. Data collection techniques in this study include interviews, observations, and documentation studies. The results of the study show that: (1) in Junior High School 7 Bandung applied LMS SIMPAI 7 as a learning tool due to changes in the learning system, limited time allocation, and the availability of ICT-based learning facilities; (2) the process of managing LMS SIMPAI 7 carried out by IPS teachers includes planning, implementation, and evaluation: (3) The effectiveness of the implementation of LMS SIMPAI 7 is categorized as sufficient, especially in terms of improving students' understanding and learning outcomes; and (4) perceived obstacles in implementing LMS SIMPAI 7 such as delays in collecting assignments and websites that are difficult to access.